Heavy metal profile, mobility, and source characterization in size-fractionated bed-sediments of River Ganga, India. (March 2023) - Radhakrishnan, Naveen; Taneja, Sonam; Ambastha, Saurav; Pipil, Harsh; Haritash, Anil Kumar
Abstract: Sediment quality assessment is vital while assessing the quality of rivers since sediments can alter the water quality depending on pH, redox conditions, and other physico-chemical characteristics. The present study aims to assess the heavy metal concentration in the size-fractionated sediments of River Ganga, and ascertain the sources of contamination in upper Himalayan stretch of around 300 km. The bed sediments of River Ganga were collected from Gomukh, Bhojwasa, Gangotri, Jhala Bridge, Chinyalisaur, Devaprayag, and Rishikesh; and these were size-fractionated in the range of 0–75, 75–150, 150–200, 200–250, 350–300, 300–450, 450–600 μm particle size to determine the concentration of heavy metals associated with each range of particle size using Atomic Absorption Spectrophotometer (AAS). The mean concentration of the metals in the sediments varied in the order Al (126 g/kg) > Fe (68 g/kg) > Cr (79 mg/kg) > Zn (67 mg/kg) > Pb (59 mg/kg) > Ni (38 mg/kg) > Cu (36 mg/kg) > Cd (2 mg/kg), and representing more affinity of metals with finer particle size of sediments. Contamination Factor and Metal Enrichment Factor indicated that sediments in the lower stretch were contaminated and enriched with many toxic metals. Geo-accumulation index, Sediment Pollution Index, and Pollution Load Index revealed that the sediments of Chinyalisaur, Devaprayag, and Rishikesh were moderately to strongly polluted and are progressively getting deteriorated by metals, thus, classifying these locations as hotspots of contamination. The major sources of Al and Fe were found to be natural; whereas Cr, Zn, Pb, Ni, Cu and Cd were mainly contributed by anthropogenic sources. The study stresses for immediate interventions to control further contamination by restricting addition of wastewater directly to River Ganga, or through other streams in Ganga basin. Highlights: Higher concentration of metals associated with finer particle-size of sediments results in long ranger transfer of toxicity Sediment-bound heavy metal concentration significantly above the Threshold Effect Level in Himalayan stretch of River Ganga Relatively higher mobility of Zn, Cr and Cu compared to Ni, Pb and Cd; and increasing anthropogenic input down the stretch